Response of growth and yield traits of Vigna radiata L. to organic fertilization and foliar application of nano copper - Husam Kadum Abbas; Mahmood N. Hussein Al-Yasari (Journal of Kerbala for Agricultural Sciences, 2024)
A study was conducted in the spring of 2023 in Karbala Governorate to examine the effects of liquid organic fertilizer and nano copper spray on the growth and yield mung beans in clay loam soil. The experiment used a randomized complete block design (RCBD) with treatments distributed in three replicates. The study looked at two factors: levels of liquid organic fertilizer (0, 10, and 2 L ha-1) and concentrations of nano copper (0, 15, 30, and 45 mg L-1). The results showed that using liquid organic fertilizer and nano copper spray, either alone or in combination, significantly impacted the growth and yield characteristics of the mung beans. The combination of liquid organic fertilizer (10 L ha-1) and nano copper spray (45 mg L-1) resulted in significant increase in the number of branches in a plant, number of leaves in a plant, leaf chlorophyll index (SPAD), plant biological yield, harvest index, and protein yield by 68.70%, 62.85%, 39.44%, 93.28%, 38.51% and 454.78% respectively, compared to the treatment without these additions.